A general model for 6 switch voltage source inverter. Issue 1 (2nd January 2017) - Verbelen, Florian; Derammelaere, Stijn; Debruyne, Colin; Stockman, Kurt
Abstract: While simulating electrical systems it is often important to determine all the current and voltage signals in a 6 switch voltage source inverter. Typically, the inverter model structure depends on the application it has to supply. As a consequence only a limited number of switching state combinations are modeled. Simulation software often offers black box blocks able to handle all switching states. However, such methods often involve iterative solvers because the voltage and current signals affect each other which results in a high computational cost. In this paper, a general model, which considers all possible switching states is introduced. Using this model it is possible to determine all current and voltage signals using only one single matrix inverse regardless of the application and with a reasonable computational effort. Both balanced and unbalanced time dependent load behavior can be considered. The model is validated with measurements on a test setup with an unbalanced load and a brushless DC motor.